2020
DOI: 10.1186/s12904-020-00666-2
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method evaluation of a volunteer navigation intervention for older persons living with chronic illness (Nav-CARE): findings from a knowledge translation study

Abstract: Background Volunteer navigation is an innovative way to help older persons get connected to resources in their community that they may not know about or have difficulty accessing. Nav-CARE is an intervention in which volunteers, who are trained in navigation, provide services for older persons living at home with chronic illness to improve their quality of life. The goal of this study was to evaluate the impact of Nav-CARE on volunteers, older persons, and family participating across eight Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…A large mixed-methods study that trialed Nav-CARE in eight sites across three Canadian provinces found it benefited older adults [38,39,41]. The qualitative portion of this study conducted semi-structured individual and group interviews with participants who had delivered or managed Nav-CARE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large mixed-methods study that trialed Nav-CARE in eight sites across three Canadian provinces found it benefited older adults [38,39,41]. The qualitative portion of this study conducted semi-structured individual and group interviews with participants who had delivered or managed Nav-CARE.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from the field of implementation science indicates innovations need to be tailored to the context where they are being implemented [37]. Our study supplemented data from a larger study [38,39] with stakeholder interviews in a single community to explore context-specific factors affecting successful implementation within that community; it focused on the inner and outer setting domains in the CFIR framework. The rationale for focusing on the inner and outer setting domains was an interest in understanding how organizational support for Nav-CARE and links between organizations affected implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteers feel well-prepared and satisfied in their role; older persons and families who have participated in the program have indicated that having a volunteer navigator has improved their engagement with life, their ability to manage their illness, and their overall quality of life. 21 Such results may hold promise for a similar model that can assist family caregivers of children living with medical complexity. The research described in this paper is a first step in preparing such an adaptation.…”
Section: Volunteer Navigationmentioning
confidence: 97%
“…20 This model, called Nav-CARE (Navigating-Connecting, Advocating, Resourcing, Engaging) provides additional training to hospice volunteers to enable them to provide assistance for the day-to-day challenges experienced by persons living with declining health at home with an emphasis on improving their quality of life. 20,21 Nav-CARE has been implemented and evaluated in multiple sites across Canada with good impact. Volunteers feel well-prepared and satisfied in their role; older persons and families who have participated in the program have indicated that having a volunteer navigator has improved their engagement with life, their ability to manage their illness, and their overall quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Pesut B. pointed out that intelligent video surveillance system, as a higher-end video surveillance application, can solve a series of problems such as management, forensics and so on. It combines machine vision algorithm with traditional video surveillance system by virtue of computer's powerful computing ability and data processing ability, thus improving the intelligent processing ability of surveillance system (Pesut B et al, 2020). Pi J. et al pointed out that in the development of agricultural remote monitoring; video technology plays a direct role in determining the quality of monitoring.…”
Section: Introductionmentioning
confidence: 99%